Comparison of clinical characteristics between COVID-19 and H7N9 fatal cases: An observational study - Jiang, Hui; Liu, Fangchao; Chan, Ta-Chien; Yin, Jinfeng; Huang, Ruowen; Shen, Li; Tu, Shengjin; Kang, Liang; Liu, Wen; Zhao, Na; Zhang, Di; Xu, Wangli; et al. (Frontiers in Public Health, 2022)
Objective To compare the clinical features and survival factors of fatal cases of COVID-19 and H7N9. Methods Data on confirmed COVID-19 and H7N9 fatal cases identified in mainland China were analyzed to compare demographic characteristics and clinical severity. Survival curves were estimated by the Kaplan-Meier method, and compared by using log-rank test and restricted mean survival time model. Cox regression models were used to identify the survival factors of fatal cases of COVID-19 and H7N9, respectively. Results Similar demographic characteristics was observed in fatal cases of COVID-19 and H7N9. The proportion of H7N9 fatal cases receiving antibiotics, antiviral drugs and oxygen treatment was higher than that of COVID-19 fatal cases. Receiving antibiotics (HR: 0.37, 95% CI:0.22-0.61), oxygen treatment (HR: 0.66, 95% CI:0.44-0.99), and corticosteroids (HR: 0.46, 95% CI:0.35-0.62) were the potential protective factors for COVID-19 fatal cases. In contrast, antiviral drug (HR: 0.21, 95% CI:0.08-0.56) and corticosteroids (HR: 0.45, 95% CI:0.29-0.69) were the protective factors for H7N9 fatal cases. Conclusion The proportion of males, those having one or more underlying medical conditions, and older age were high in COVID-19 and H7N9 fatal cases. Offering antibiotics, oxygen treatment and corticosteroids to COVID-19 cases extended the survival time. Continued global surveillance remains an essential component of pandemic preparedness.